Top‐Ranked Priority Research Questions for Soil Science in the 21st Century. Issue 2 (3rd February 2014) - Adewopo, Julius B.; VanZomeren, Christine; Bhomia, Rupesh K.; Almaraz, Maya; Bacon, Allan R.; Eggleston, Emily; Judy, Jonathan D.; Lewis, Ricky W.; Lusk, Mary; Miller, Bradley; Moorberg, Colby; Snyder, Elizabeth Hodges; et al.
Abstract : Soils provide critical support essential for life on earth, regulate processes across diverse terrestrial and aquatic ecosystems, and interact with the atmosphere. However, soil science is constrained by a variety of challenges including decreasing funding prospects and a declining number of new students and young professionals. Hence, there is a crucial need to revitalize the impact, relevance, and recognition of soil science as well as promote collaboration beyond traditionally defined soil science research disciplines. Such revitalization and collaboration may be fostered by a shift from discipline‐focused soil science research to cross‐disciplinary research approaches and issue‐driven research. In this paper, we present the outcomes of an initiative to identify priority research questions as a tool for guiding future soil science research. The collaborative approach involved four stages including (i) survey‐based solicitation of questions; (ii) criteria‐based screening of submitted candidate questions, (iii) criteria‐based ranking of screened questions, and (iv) final revision of top ranked questions. The 25 top ranked research questions emerged from 140 submitted candidate questions within five predetermined thematic areas that represent current and emerging research areas. We expect that the identified questions will inspire both existing and prospective researchers, enhance multi‐disciplinary collaboration both within and outside soil science, draw the attention of grant‐awarding bodies, and guide soil science research to address pressing societal, agricultural, and environmental challenges. Furthermore, we hope that the approach and findings presented in this paper will advance soil sciences by fostering improved collaboration among soil science practitioners and researchers, as well as with other sciences, policy experts, and emerging professionals (including students) to meet societal needs.